Performance evaluation of manet in presence of black hole nodes - Dhahir, Saif Mahmood (2017)
Mobile ad-hoc network (MANET) is a standout amongst the most dynamic exploration subjects amid the earlier years. Mobile Ad-hoc networks are wireless, self-configurable as well as infrastructure-less networks which, can help in communicating information from one node to another using the intermediate nodes as a router. As the devices have mobility here, the network is dynamic in nature and it is quite often to re-establish the connection again and again. Because of the environment of ad-hoc network, dynamic, infrastructure-less and self-organizing, MANETs are vulnerable to several kinds of attacks and the black hole is one of the network layer attacks. In this type of attack, the black hole node uses the maximum destination sequence number to lure the sender node, to send packets via the shortest path, so that it will drop or alter the packets intentionally instead of sending them to the destination. Thus, the black hole nodes will reduce the network performance. The major goal of our project is to evaluate the performance of MANETs with and without the black hole node. Network simulator NS2.34 used for the simulation of the network within three different number mobile nodes (50, 150, and 165). The parameters used for evaluating the network performance are packet delivery ratio, an end-to-end delay, throughput and packet drop. The evaluation of two different scenarios using AODV routing protocol such as varying the number of black hole nodes and different mobility speed of the nodes. The analysis of generated trace files can be performed with the help of awk script. And then we will apply an algorithm that can offer better performance evaluation of the MANET compare to previous work[1]. Keyword: black hole attack, AODV routing protocol, MANETs, performance metrics.